The effects of elevated pain inhibition on endurance exercise performance - Flood, Andrew; Waddington, Gordon; Keegan, Richard J.; Thompson, Kevin G.; Cathcart, Stuart (PeerJ, 2017)
Background The ergogenic effects of analgesic substances suggest that pain perception is an important regulator of work-rate during fatiguing exercise. Recent research has shown that endogenous inhibitory responses, which act to attenuate nociceptive input and reduce perceived pain, can be increased following transcranial direct current stimulation of the hand motor cortex. Using high-definition transcranial direct current stimulation (HD-tDCS; 2 mA, 20 min), the current study aimed to examine the effects of elevated pain inhibitory capacity on endurance exercise performance. It was hypothesised that HD-tDCS would enhance the efficiency of the endogenous pain inhibitory response and improve endurance exercise performance. Methods Twelve healthy males between 18 and 40 years of age (M = 24.42 ± 3.85) were recruited for participation. Endogenous pain inhibitory capacity and exercise performance were assessed before and after both active and sham (placebo) stimulation. The conditioned pain modulation protocol was used for the measurement of pain inhibition. Exercise performance assessment consisted of both maximal voluntary contraction (MVC) and submaximal muscular endurance performance trials using isometric contractions of the non-dominant leg extensors. Results Active HD-tDCS (pre-tDCS, −.32 ± 1.33 kg; post-tDCS, −1.23 ± 1.21 kg) significantly increased pain inhibitory responses relative to the effects of sham HD-tDCS (pre-tDCS, −.91 ± .92 kg; post-tDCS, −.26 ± .92 kg; p = .046). Irrespective of condition, peak MVC force and muscular endurance was reduced from pre- to post-stimulation. HD-tDCS did not significantly influence this reduction in maximal force (active: pre-tDCS, 264.89 ± 66.87 Nm; post-tDCS, 236.33 ± 66.51 Nm; sham: pre-tDCS, 249.25 ± 88.56 Nm; post-tDCS, 239.63 ± 67.53 Nm) or muscular endurance (active: pre-tDCS, 104.65 ± 42.36 s; post-tDCS, 93.07 ± 33.73 s; sham: pre-tDCS, 123.42 ± 72.48 s; post-tDCS, 100.27 ± 44.25 s). Discussion Despite increasing pain inhibitory capacity relative to sham stimulation, active HD-tDCS did not significantly elevate maximal force production or muscular endurance. These findings question the role of endogenous pain inhibitory networks in the regulation of exercise performance.
Keywords: HD-tDCS; CPM; Exercise performance; Pain inhibition